SKIPPING DISCOVERY? MUSIC DISCOVERY AND PERSONAL MUSIC COLLECTIONS IN THE STREAMING ERA - Ellis, Jack Michael (AoIR Selected Papers of Internet Research, 2020)
In this paper, I use Spotify as a case study to investigate user experiences of music exploration and discovery using streaming services and recommendation algorithms. Following the framing of music discovery as an affective response which allows for the categorization and definition of music, I draw upon qualitative data from Spotify users regarding their ephemeral experiences when exploring music using streaming services. I identify user practices of music archiving and collecting as a strategy to mitigate these transient encounters by slowing down the pace of their music consumption and creating enduring connections between music and their individual histories. In this way, personal music collections were found to support instances of music discovery as they created a listening context and user mindset which was sympathetic the affective definition and categorization of new music content. This investigation of collecting practice also revealed longitudinal perspectives on music discoveries which emerge through sustained listening over time, drawing attention to listener’s social surroundings, friends and online communities as the impetus for choosing to give particular music content time to grow towards being discovered. The paper concludes with implications of the use of algorithmic recommendation systems in the delivery and consumption of music and other cultural forms.